Professional Development Practices and Work Performance of Teachers in Public Secondary Schools - Cerafica, Mylyn (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study investigated the professional development practices and work performance of teachers in public secondary schools in the Binangonan District, Schools Division Office of Rizal, during the School Year 2025–2026. Specifically, it examined the extent of teachers’ professional development practices in terms of school engagement, research development, and community involvement, and their relationship to work performance. A descriptive survey research design, complemented by documentary analysis, was employed. The respondents consisted of 400 teachers, representing 50% of the total population, selected through simple random sampling. A researcher-made questionnaire-checklist was used to assess professional development practices, while documentary analysis of the Individual Performance Commitment and Review (IPCR) for School Year 2024–2025 served as the basis for evaluating work performance.Findings revealed that the majority of respondents were aged 31 and above, predominantly female, married, and pursuing graduate studies. Most held Teacher I and II positions, had more than 15 years of service, and participated in division- and district-level trainings. Teachers demonstrated a very high extent of professional development in school engagement and a high extent in research development and community involvement. Significant differences were found in professional development practices when grouped according to age, position title, and in-service trainings attended, while no significant differences were observed in terms of sex, civil status, educational attainment, and length of service. Teachers’ work performance was rated very satisfactory and showed a significant relationship with their professional development practices.The study concluded that professional development practices significantly influence teachers’ work performance. It is recommended that school administrators continuously support professional growth initiatives, encourage participation in trainings, and promote institutional linkages. Implementation of the proposed action plan and further studies on related variables are also suggested.
Keywords: Professional Development, Teacher Performance, School Engagement, Research Development, Community Involvement, Public Secondary Schools